Grinding behavior of austempered ductile iron: a study about the effect of pure and diluted MQL technique applying different friability wheels - Moretti, Guilherme Bressan [UNESP]; Moraes, Douglas Lyra de [UNESP]; Garcia, Mateus Vinicius [UNESP]; Lopes, Jose Claudio [UNESP]; Ribeiro, Fernando Sabino Fonteque; Foschini, Cesar Renato [UNESP]; Mello, Hamilton Jose de [UNESP]; Sanchez, Luiz Eduardo De Angelo [UNESP]; Aguiar, Paulo Roberto [UNESP]; Bianchi, Eduardo Carlos [UNESP] (Springer, 2020)
Abrasion machining has stood out in the current industry due to constant improvements in the dimensional accuracy of a workpiece in its finishing process. Thus, it is necessary to use cutting fluid to cool and lubricate the workpiece-wheel contact, to reduce both the high temperatures reached and the friction. However, conventional cutting fluid is harmful to the environment and poses a risk to the operator's health. As a result, the minimum lubricant quantity (MQL) technique emerged, using extremely smaller amounts of fluid and, however, showing excellent results in its applications. In this way, it could further optimize this method through studies on oil dilution, combating low cooling capacity. A fundamental concept for selecting the grinding wheel type to be used in grinding is friability, but there are few studies on its influence on the process. For these reasons, this research analyzed the impact of friability and the effects of MQL dilution on the grinding of austempered ductile iron, the use of two CBN wheels with high and low friability, and four types of lubri-refrigerant methods: flood, pure MQL, and diluted MQL in the oil-water ratio 1:5 and 1:10. Output parameters were analyzed: surface roughness (Ra), roundness error, diametrical wheel wear, cutting power, acoustic emission, viscosity, 3D confocal, and microhardness. The results show an improvement of the diluted MQL over the pure, coming close to the conventional method. Besides, the low friability wheel was more efficient in the analysis of surface roughness, roundness error, and diametrical wheel wear. However, most friable stood out in the results of acoustic emission and grinding power.
Keywords: Grinding; Pure MQL; Diluted MQL; Friability; Austempered ductile iron